2015
DOI: 10.1585/pfr.10.2404003
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Neutron Generation via Laser-Driven Photonuclear Reaction

Abstract: The generation of high-peak-intensity neutrons through a photonuclear reaction was demonstrated using the Laser for Fast Ignition Experiments (LFEX) at Osaka University. Up to 10 9 neutrons/shot were generated from a 1 mm sized gold target. Using Monte Carlo simulations, the neutron spectrum from keV to MeV was found to be independent of the γ-ray spectrum. The typical peak neutron intensity of 10 21 neutrons /cm 2 /s at the target surface was estimated, and it should be a useful tool for nuclear synthesis exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Our results may have application as an intense ultrashort electron source in the multi-MeV range, with characteristics not easily attainable with other techniques. Electrons with these parameters are potentially of interest for photoneutron generation [26][27][28] (aiming at extremely high fluxes) or ultra-fast electron diffraction [29][30][31] (for imaging of ultrafast processes with electron diffraction). Besides these possible applications our results confirm the possibility to extend the study and applications of plasmonics into the high field, relativistic regime.…”
mentioning
confidence: 99%
“…Our results may have application as an intense ultrashort electron source in the multi-MeV range, with characteristics not easily attainable with other techniques. Electrons with these parameters are potentially of interest for photoneutron generation [26][27][28] (aiming at extremely high fluxes) or ultra-fast electron diffraction [29][30][31] (for imaging of ultrafast processes with electron diffraction). Besides these possible applications our results confirm the possibility to extend the study and applications of plasmonics into the high field, relativistic regime.…”
mentioning
confidence: 99%
“…Repetitive neutron generation is essential for some applications that require not only high peak intensity but also high average flux of the neutron beam. Several authors reported laser-driven neutron generations [5] based on nuclear fusion reactions by laser-driven implosion [6,7], nuclear interactions of light atoms with protons and/or deuterons accelerated by high-intensity laser pulse [8,9], and photonuclear reactions of matters with high energy photons generated by laser-matter interactions [10,11]. National Ignition Facility (NIF), which is the world largest laser facility delivering up to 1.8 MJ of laser energy, achieved more than 10 16 neutron yield per pulse by deuterium and tritium nuclear fusion reactions [6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above candidates, there are other neutron sources utilizing a laser [9] or inertial electrostatic confinement [10]. However they does not give appropriate pulsed neutrons for NRTA measurement at present.…”
Section: Concept Of a Compact Nrta Systemmentioning
confidence: 99%